Review of All the right stuff (directed by C. Littlefield), Lost borders (directed and produced by K. Shelton), and It takes a child: Craig Kielburger’s study: A journey into child labour - Bereska, Tami (My University, 2000)
These three videos represent something that is relatively rare in the social sciences; they are all high quality, well-produced videos that look at the lives of youth in contemporary society. Rather than falling into the all-too-frequent trap of treating adolescents as part of some circus freak show that we are privy to watch, these videos show the lives of ordinary youth living in extraordinary times. Taken together, these three videos illustrate the important fact that while we tend to group all adolescents together under the generic umbrella of ‘youth culture’ or ‘youth subculture’, not all youth are the same. Each video focuses on a particular segment of youth culture and/or a particular set of experiences within youth culture.
Keywords: youth culture; adolescents